2017
DOI: 10.1136/bmjpo-2017-000191
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in child and adolescent physical morbidity: cohort study

Abstract: BackgroundEvidence on sex differences in physical morbidity in childhood and adolescence is based largely on studies employing single/few physical morbidity measures and different informants. We describe sex differences in a wide range of parent/carer-reported physical morbidity measures between ages 4 and 13 years to determine evidence for a generalised pattern of an emerging/increasing female ‘excess’.MethodsParents/carers (approximately 90% mothers) of the population-based UK ALSPAC cohort provided data on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 30 publications
0
20
0
Order By: Relevance
“…44, 1.88, 2.70], stomachaches [ORs=1.64, 2.00, 2.31], and backaches [ORs=1.16, 1.24, 1.28] (Cavallo et al, 2006). Likewise, the English ALSPAC study found that beginning with the youngest children in their study (age 4 years), girls reported more headaches, stomachaches and earaches than boys did (Sweeting et al, 2017). Chronic pain also was reported in childhood by females more than males (Fillingim et al, 2009).…”
Section: Preventing Injury Through the Sensation Of Pain Pain Signals Potential Danger Or Actual Damagementioning
confidence: 96%
See 1 more Smart Citation
“…44, 1.88, 2.70], stomachaches [ORs=1.64, 2.00, 2.31], and backaches [ORs=1.16, 1.24, 1.28] (Cavallo et al, 2006). Likewise, the English ALSPAC study found that beginning with the youngest children in their study (age 4 years), girls reported more headaches, stomachaches and earaches than boys did (Sweeting et al, 2017). Chronic pain also was reported in childhood by females more than males (Fillingim et al, 2009).…”
Section: Preventing Injury Through the Sensation Of Pain Pain Signals Potential Danger Or Actual Damagementioning
confidence: 96%
“…In a large study of Norwegian adolescents (n=10,000, ages 17-19 years), 47% of girls versus 21% of boys [OR=3.34] reported at least one weekly health complaint (Myrtveit Saether et al, 2018) (Cavallo et al, 2006). Likewise in the Avon Longitudinal Study of Parents and Children (ALSPAC) (n>13,900), pregnant women in 1991-1992 in Southwestern England were recruited and later asked to report symptoms experienced by their 4-13 year-old children (Sweeting et al, 2017). From 4 years onwards, more girls than boys experienced colds, cold sores, tonsillitis, urinary infections, earaches, headaches, stomachaches, worm infections, head lice or scabies, constipation, and eczema.…”
Section: Immune Defensesmentioning
confidence: 99%
“…The WHO HBSC study in 32 countries in Europe, North America, and Israel (n > 150,000) found that more girls than boys experienced headaches at age 11, 13, and 15 years respectively (ORs = 1.44, 1.88, 2.70), stomachaches (ORs = 1.64, 2.00, 2.31), and backaches (ORs = 1.16, 1.24, 1.28) (Cavallo et al, 2006). Likewise, the English ALSPAC study found that beginning with the youngest children in their study (age 4 years), girls reported more headaches, stomachaches, and earaches than boys did (Sweeting et al, 2017). Chronic pain also was reported in childhood by females more than males .…”
Section: Preventing Injury Through the Sensation Of Painmentioning
confidence: 91%
“…Employing the Health Behaviour in School-Aged Children (HBSC) scale, a WHO study in 32 countries in Europe and North America plus Israel (n = 1,500 each nation at ages 11, 13, and 15 years, n > 150,000) found that girls reported poorer general health than boys at ages 11 (OR = 1.36), 13 (OR = 1.68), and 15 years (OR = 1.97) (Cavallo et al, 2006). Likewise in the Avon Longitudinal Study of Parents and Children (ALSPAC) (n > 13,900), pregnant women in 1991-1992 in Southwestern England were recruited and later asked to report symptoms experienced by their 4-13-year-old children (Sweeting, Whitley, Teyhan, & Hunt, 2017). From 4 years onwards, more girls than boys experienced colds, cold sores, tonsillitis, urinary infections, earaches, headaches, stomachaches, worm infections, head lice or scabies, constipation, and eczema.…”
Section: Immune Defensesmentioning
confidence: 99%
“…Employing the Health Behaviour in School-Aged Children (HBSC) scale, a WHO study in 32 countries in Europe and North America plus Israel (n = 1,500 each nation at ages 11, 13, and 15 years, n > 150,000) found that girls reported poorer general health than boys at ages 11 (OR = 1.36), 13 (OR = 1.68), and 15 years (OR = 1.97) (Cavallo et al, 2006). Likewise in the Avon Longitudinal Study of Parents and Children (ALSPAC) (n > 13,900), pregnant women in 1991-1992 in Southwestern England were recruited and later asked to report symptoms experienced by their 4-13-year-old children (Sweeting, Whitley, Teyhan, & Hunt, 2017). From 4 years onwards, more girls than boys experienced colds, cold sores, tonsillitis, urinary infections, earaches, headaches, stomachaches, worm infections, head lice or scabies, constipation, and eczema.…”
Section: Immune Defensesmentioning
confidence: 99%